Normativity as Pitfall or Ally? - Kaufman, Tone Stangeland (Ecclesial practices, 2015)
When theologians, who care about church, spirituality, and theology, conduct empirical, ecclesiological studies, our underlying normative values impact the entire research process and results in unhelpful or helpful ways. In this article I propose that attending to precisely reflexivity might change our initial, naïve normativity from an implicit to an explicit normativity. I suggest that if these normative values are brought to the table, and self-critically and honestly reflected on, the initially naïve normativity can prove to be an interpretive key in unlocking the data, thus helping us understand the phenomenon under investigation in a more nuanced way. When making this claim, I mainly draw on my own empirical study on clergy spirituality in the Church of Norway (CofN), but also bring in the work of other scholars, and in particular Mary McClintock Fulkerson’s ethnographic work and “theology in four voices” proposed by the arcs team.